The Expression of Love in Marriage / Margareta Jelić - Jelić, Margareta (2012)
The lecture provides a cross-cultural look at the ways husbands and wives express love in marriage. The presentation relies on the international data set comprised of 926 married couples (302 Croatian, 456 Serbian, and 168 from the United States). These data represent one of the first empirical examinations of marital love in Southern Europe and shed light on an often overlooked topic—the behavioral manifestation of love. An important question addressed will be whether love is associated with different behaviors for husbands and wives, and whether husbands and wives express love differently in Croatia, Serbia, and the United States. Further more, a new scale will be presented, a self-report measure based on qualitative research that assesses individuals’ tendency to express love through six clusters of behaviors. Additionally, preliminary data with the new scale offers answers to some relevant questions such as whether there are gender differences in the ways of showing love, whether spouses’ reported displays of love are perceived as such by their partner, and if shared perceptions are tied to higher levels of marital satisfaction.